Analisis Performansi dan Skalabilitas pada Event-Based IoT Middleware - Mohammad Fahrur Rozi; Eko Sakti Pramukantoro; Kasyful Amron (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2017)
Internet of Things (IoT) is a system where its contained devices are interconnected which makes it possible to exchange information or data via Internet. Middleware is an intermediary system between hardware and software which contained in IoT system. In the previous research, middleware was developed to overcome interoperability problem by providing multi-protocol gateway for CoAP MQTT and Websocket. There are several aspects to test middleware such as integration, interoperability, scalability, real time performance, and security. In the previous research, integration testing was performed to test the suitability of middleware with its functional requirements and interoperability testing in order to know the level of middleware interoperability, therefore in this research a test performed with other aspects which is performance and scalability. The results of performance and scalability analysis are average CPU usage of CoAP protocol was 0.68%, MQTT 0.60% and CoAP MQTT 1.21%, average Memory usage of CoAP was 5-7%, MQTT 8-9%, and CoAP MQTT 10-12%. The average delay time of sending data from nodeMCU to middleware for CoAP and MQTT is 3 seconds. The average data transmission delay time from nodeMCU to middleware with packet loss is varied between 0% - 75%. The ability of middleware to overcome publish or subscibe in one second with 100 to 1000 clients grows as the number of clients increases.